Endophytic Colonization of Rice by a Diazotrophic Strain of Serratia marcescens - Gyaneshwar, Prasad (American Society for Microbiology, 2001)
Six closely related N(2)-fixing bacterial strains were isolated from surface-sterilized roots and stems of four different rice varieties. The strains were identified as Serratia marcescens by 16S rRNA gene analysis. One strain, IRBG500, chosen for further analysis showed acetylene reduction activity (ARA) only when inoculated into media containing low levels of fixed nitrogen (yeast extract). Diazotrophy of IRBG500 was confirmed by measurement of (15)N(2) incorporation and by sequence analysis of the PCR-amplified fragment of nifH. To examine its interaction with rice, strain IRBG500 was marked with gusA fused to a constitutive promoter, and the marked strain was inoculated onto rice seedlings under axenic conditions. At 3 days after inoculation, the roots showed blue staining, which was most intense at the points of lateral root emergence and at the root tip. At 6 days, the blue precipitate also appeared in the leaves and stems. More detailed studies using light and transmission electron microscopy combined with immunogold labeling confirmed that IRBG500 was endophytically established within roots, stems, and leaves. Large numbers of bacteria were observed within intercellular spaces, senescing root cortical cells, aerenchyma, and xylem vessels. They were not observed within intact host cells. Inoculation of IRBG500 resulted in a significant increase in root length and root dry weight but not in total N content of rice variety IR72. The inoculated plants showed ARA, but only when external carbon (e.g., malate, succinate, or sucrose) was added to the rooting medium.